Can innovations in agri-food systems deliver gender equity and resilience? - Johnstone, Kevin; Aung, May Thazin; Barrett, Sam (International Institute for Environment and Development, 2023)
Agri-food systems constitute a huge proportion of global jobs and economies, but are failing to provide healthy diets, equitable livelihoods and sustainable practices. Women in rural areas are highly prominent in the sector and most vulnerable to climate impacts.